EXECUTION OF AUCTION ON MORTGAGE RIGHTS FOR PRODUCTIVE FINANCING DUE TO DEFAULT BECAUSE OF PANDEMIC IMPACT AT BANK SULSELBAR SHARIA MAROS BRANCH : ANALYSIS OF ISLAMIC LAW - Nurvadillah, Nurvadillah; Lutfi, Mukhtar; Haddade, Abdul Wahid (International Journal of Islamic Studies, 2022)
Every financial transaction in Sharia Banking is required to include a guarantee. This thing is to save the bank funds when customer does a default. The Sharia Bank based on Law number 4 of 1996 concerning the Mortgage rights have the rights to confiscate customer guarantees that have matured and there is no good willingness to pay. However, in practice, banks cannot carry out execution practices to make sales directly. Banks have to go through a long formal procedure to withdraw funds from the customer guarantees, and often encounter various kinds of obstacles. Researchers use two data sources, namely a primary data and secondary data. Methods of data collection, researchers conducted interviews and documentation observations. Data analysis by following the steps namely data display, data reduction, data editing, data analysis, and drawing conclusions. Testing of the validity of data in this research is triangulation of data sources and triangulation of methods.